A preparation method of high-density sodium iron pyrophosphate positive electrode material and vehicle

Through the preparation method of high-pressure sodium iron pyrophosphate positive electrode material, the problem of low performance parameters of sodium ion battery is solved, and a positive electrode material with high compaction density and reversible capacity is achieved, which improves the energy density and cycle stability of sodium ion battery.

CN119349541BActive Publication Date: 2025-04-15ZHEJIANG HUAYU NADIAN NEW ENERGY TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411943191.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-15
Estimated Expiration
2044-12-27

AI Technical Summary

Technical Problem

The electrochemical reaction kinetics of sodium ion batteries are slow, have large volume changes, and have low cycle stability, rate performance and energy density, which limit their commercial applications.

Method used

Using the preparation method of high-pressure sodium ferric pyrophosphate positive electrode material, a positive electrode material with high compaction density and reversible capacity is prepared by mixing metal compounds, non-metallic compounds, second phase nanoparticles with deionized water, adding slurry aid dispersant, and stirring at high speed.

Benefits of technology

The compaction density and reversible capacity of the high-pressure sodium ferric pyrophosphate positive electrode material are improved, the conductivity and cyclic stability of the electrode are enhanced, and the energy density of the sodium ion battery is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119349541B_ABST
    Figure CN119349541B_ABST
Patent Text Reader

Abstract

A method for preparing a high-density sodium iron phosphate pyrophosphate positive electrode material and a vehicle, belonging to the technical field of synthesis of positive electrode materials for sodium ion batteries; the preparation method specifically includes the following steps: uniformly mixing a metal compound, a non-metal compound, a second phase nanoparticle and deionized water, adding a slurry dispersant and stirring at high speed, and then sand milling, spray drying and air flow crushing to obtain a high-density sodium iron phosphate pyrophosphate positive electrode material, and applying the positive electrode material to a vehicle sodium ion battery; the slurry dispersant includes at least a tetraphenylethylene quaternary ammonium salt derivative and an amide pyridine compound, the tetraphenylethylene quaternary ammonium salt derivative has a vinyl group and a quaternary ammonium group, and the amide pyridine compound has an amide group and a pyridine group. The present invention is a method for preparing a high-density sodium iron phosphate pyrophosphate positive electrode material and a vehicle with high compaction density and high reversible capacity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of synthesis of positive electrode materials for sodium ion batteries, and in particular to a preparation method and a vehicle for a high-density sodium iron phosphate pyrophosphate positive electrode material. Background Art

[0002] With the rapid development of electric vehicles, energy storage and other fields, the market's requirements for battery types have gradually become diversified. In recent years, sodium-ion batteries have attracted widespread attention due to their abundant sodium resources and high safety, and are considered to be a beneficial supplement to lithium-ion batteries in the field of large-scale energy storage. However, the larger radius of sodium ions usually causes slow electrochemical reaction kinetics and large volume changes in sodium-ion batteries, and the redox potential of sodium ions is higher than that of lithium ions. These factors have caused sodium-ion batteries to be limited by unsatisfactory cycle stability, rate performance and energy density, which in turn prevents their further commercial application. The influence of positive electrode materials on the above sodium-ion battery performance parameters is crucial, among which polyanion-type positive electrode materials have been widely studied due to their open three-dimensional channels, high operating voltage and excellent structural stability. Among the many reported polyanion-type positive electrode materials, low-cost sodium iron pyrophosphate shows excellent commercial application potential. However, the low electronic conductivity of sodium iron pyrophosphate leads to its poor rate performance. In response to this problem, various performance optimization strategies have been developed and can effectively improve the rate performance of materials, such as nano-morphology design, carbon coating and ion doping, etc. However, these methods always have disadvantages such as low tap density, small volume capacity or a lot of inactive substances, which leads to low energy density of sodium iron pyrophosphate. Therefore, a new preparation method of high-pressure compacted sodium iron pyrophosphate positive electrode material is needed to solve the problems existing in this type of positive electrode material and use it in vehicles. Summary of the invention

[0003] The object of the present invention is to provide a method for preparing a high-density sodium iron phosphate pyrophosphate positive electrode material and a vehicle, so as to improve the compaction density and reversible capacity of the high-density sodium iron phosphate pyrophosphate positive electrode material.

[0004] The technical solution adopted by the present invention to achieve the above-mentioned purpose is:

[0005] A preparation method of a high-density sodium iron phosphate pyrophosphate positive electrode material comprises the following steps: uniformly mixing a metal compound, a non-metal compound, second phase nanoparticles and deionized water, adding a slurry dispersant and stirring at high speed, and then sand milling, spray drying and air flow pulverizing to obtain the high-density sodium iron phosphate pyrophosphate positive electrode material; the slurry dispersant comprises at least a tetraphenylethylene quaternary ammonium salt derivative and an amide pyridine compound, the tetraphenylethylene quaternary ammonium salt derivative has a vinyl group and a quaternary ammonium group, and the amide pyridine compound has an amide group and a pyridine group.

[0006] The invention mixes sodium acetate, ferric oxalate, ammonium dihydrogen phosphate, polyethylene glycol, sucrose, nano titanium nitride and nano zirconium dioxide, and adds tetraphenylethylene quaternary ammonium salt derivatives and amide pyridine compounds as slurry dispersants to prepare high-density sodium phosphate iron pyrophosphate positive electrode materials; the invention uses nano titanium nitride and nano zirconium dioxide as second-phase nanoparticles to prepare high-density sodium phosphate iron pyrophosphate positive electrode materials, and the nanoparticles can accelerate the embedding and extraction of ions in the electrode, and help to form a conductive network between electrode active materials, thereby enhancing the conductive performance of the electrode; the invention also uses tetraphenylethylene quaternary ammonium salt derivatives and amide pyridine compounds as slurry dispersants to prepare high-density sodium phosphate iron pyrophosphate positive electrode materials, and the tetraphenylethylene quaternary ammonium salt derivatives and amide pyridine compounds can prevent the aggregation of electrode materials through electrostatic repulsion or steric hindrance, help to form a uniform and stable electrode material, thereby improving the electrochemical performance of the electrode material.

[0007] Preferably, the tetrastyryl quaternary ammonium salt derivative is prepared by reacting 1,1-diphenyl-2,2-di(4-bromophenyl)ethylene with N-(3-(dimethylamino)propyl)octanamide.

[0008] Preferably, the amidopyridine compound is prepared by first reacting ethyl isonicotinate with 1,6-diaminohexane and then reacting with 1,4-dichlorobutane.

[0009] Preferably, the metal compound comprises sodium acetate and ferric oxalate, and the mass ratio of sodium acetate to ferric oxalate is 1:2-10.

[0010] Preferably, the non-metallic compound comprises diammonium phosphate, polyethylene glycol and sucrose, the mass ratio of polyethylene glycol to diammonium phosphate is 1:20-40, and the mass ratio of sucrose to diammonium phosphate is 1:20-40.

[0011] Preferably, the second phase nanoparticles include nano-titanium nitride and nano-zirconium dioxide, and the mass ratio of nano-titanium nitride to nano-zirconium dioxide is 1:1-2.

[0012] Preferably, the mass ratio of the tetrastyryl quaternary ammonium salt derivative to the amide pyridine compound is 1:1-2.

[0013] Preferably, the preparation method of the tetraphenylethylene quaternary ammonium salt derivative is specifically as follows:

[0014] 1,1-diphenyl-2,2-di(4-bromophenyl)ethylene and N-(3-(dimethylamino)propyl)octanamide were mixed, acetone was added, and the mixture was heated under reflux for 36-72 hours, and then rotary evaporated and vacuum dried to obtain a tetraphenylethylene quaternary ammonium salt derivative.

[0015] More preferably, the molar ratio of 1,1-diphenyl-2,2-di(4-bromophenyl)ethylene to N-(3-(dimethylamino)propyl)octanamide is 1:1-5.

[0016] More preferably, the usage ratio of 1,1-diphenyl-2,2-di(4-bromophenyl)ethylene and acetone is 1 mmol:0.5-5 mL.

[0017] Preferably, the method for preparing the amide pyridine compound comprises:

[0018] Ethyl isonicotinate and 1,6-diaminohexane are mixed, sodium methoxide solution and toluene are added, reflux reaction is carried out for 8-24 hours, 1,4-dichlorobutane and N,N-dimethylformamide are added, heating is carried out at 100-150° C. for 8-24 hours, a recrystallization agent is added, and recrystallization is carried out for 2-5 times to obtain an amide pyridine compound.

[0019] More preferably, the molar ratio of ethyl isonicotinate to 1,6-diaminohexane is 1:0.2-1.

[0020] More preferably, the mass concentration of the sodium methoxide solution is 10-50%, and the usage ratio of ethyl isonicotinate to the sodium methoxide solution is 1 mol: 50-200 mL.

[0021] More preferably, the volume ratio of the sodium methoxide solution to toluene is 1:2-20.

[0022] More preferably, the molar ratio of ethyl isonicotinate to 1,4-dichlorobutane is 1:1-5.

[0023] More preferably, the volume ratio of the sodium methoxide solution to N,N-dimethylformamide is 1:2-20.

[0024] More preferably, the volume ratio of toluene to the recrystallization agent is 1:1-3, the recrystallization agent includes acetone and methanol, and the volume ratio of acetone to methanol is 1:1-2.

[0025] Preferably, a method for preparing a high-density sodium iron phosphate pyrophosphate positive electrode material comprises:

[0026] Sodium acetate, ferric oxalate, ammonium dihydrogen phosphate, polyethylene glycol, sucrose, nano titanium nitride and nano zirconium dioxide are added to deionized water and mixed and stirred. The mixture is dispersed at a high speed for 20-60 minutes, and the mixture is treated at a sand mill speed of 1000-2000 rpm for 1-5 hours until the mixture is evenly dispersed and the D50 particle size is 160-200 nm. The mixture is spray dried at a feed rate of 1-3 L / h at 200-250° C., and then the temperature is increased to 500-550° C. at a rate of 0-4° C. / min in a nitrogen atmosphere and sintered for 12-36 hours. The particles are crushed to a D50 particle size of 4-5 μm by air flow crushing to obtain a high-density sodium iron phosphate pyrophosphate positive electrode material.

[0027] More preferably, the mass ratio of sodium acetate to ferric oxalate is 1:1-5.

[0028] More preferably, the mass ratio of sodium acetate to diammonium phosphate is 1:0.5-3.

[0029] More preferably, the mass ratio of polyethylene glycol to diammonium phosphate is 1:20-40.

[0030] More preferably, the mass ratio of sucrose to diammonium phosphate is 1:20-40.

[0031] More preferably, the mass ratio of sodium acetate to nano-titanium nitride is 1:0.005-0.015.

[0032] More preferably, the mass ratio of nano-titanium nitride to nano-zirconium dioxide is 1:1-2.

[0033] More preferably, the usage ratio of sodium acetate to deionized water is 1 g: 2-10 mL.

[0034] Preferably, a method for preparing a high-density sodium iron phosphate pyrophosphate positive electrode material comprises:

[0035] Sodium acetate, ferric oxalate, ammonium dihydrogen phosphate, polyethylene glycol, sucrose, nano titanium nitride and nano zirconium dioxide are added to deionized water and mixed and stirred. A slurry dispersant is added, and the mixture is dispersed with high-speed stirring for 20-60 minutes. The mixture is treated with a sand mill at a speed of 1000-2000 rpm for 1-5 hours until it is evenly dispersed and the D50 particle size is 160-200 nm. The mixture is spray dried at a feed rate of 1-3 L / h at 200-250° C., and then the temperature is increased to 500-550° C. at a rate of 0-4° C. / min in a nitrogen atmosphere and sintered for 12-36 hours. The particles are crushed to a D50 particle size of 4-5 μm by air flow crushing to obtain a high-density sodium iron phosphate pyrophosphate positive electrode material.

[0036] More preferably, the mass ratio of sodium acetate to ferric oxalate is 1:1-5.

[0037] More preferably, the mass ratio of sodium acetate to diammonium phosphate is 1:0.5-3.

[0038] More preferably, the mass ratio of polyethylene glycol to diammonium phosphate is 1:20-40.

[0039] More preferably, the mass ratio of sucrose to diammonium phosphate is 1:20-40.

[0040] More preferably, the mass ratio of sodium acetate to nano-titanium nitride is 1:0.005-0.015.

[0041] More preferably, the mass ratio of nano-titanium nitride to nano-zirconium dioxide is 1:1-2.

[0042] More preferably, the usage ratio of sodium acetate to deionized water is 1 g: 2-10 mL.

[0043] More preferably, the mass ratio of sodium acetate to the slurry dispersant is 1:0.06-0.1.

[0044] More preferably, the slurry dispersant comprises tetrastyryl quaternary ammonium salt derivatives and amide pyridine compounds.

[0045] More preferably, the mass ratio of the tetrastyryl quaternary ammonium salt derivative to the amide pyridine compound is 1:0.5-1.

[0046] Preferably, a method for preparing a high-density sodium iron phosphate pyrophosphate positive electrode material further uses polyethylene glycol triphenylphosphine as a slurry dispersant. The slurry dispersant includes a tetraphenylethylene quaternary ammonium salt derivative, an amide pyridine compound and polyethylene glycol triphenylphosphine. The use of polyethylene glycol triphenylphosphine can not only further increase the compaction density of the electrode, thereby increasing the energy density of the electrode; but also can further improve the dispersion stability of the electrode, and enhance the conductivity and reversible capacity of the electrode.

[0047] More preferably, the mass ratio of the tetrastyryl quaternary ammonium salt derivative to the amide pyridine compound is 1:0.5-1.

[0048] More preferably, the mass ratio of the tetrastyryl quaternary ammonium salt derivative to polyethylene glycol triphenylphosphine is 1:0.25-0.5.

[0049] The invention also discloses a high-density sodium iron phosphate pyrophosphate positive electrode material prepared by the method.

[0050] The invention also discloses a sodium ion battery, comprising a sodium ion battery positive electrode sheet, a sodium sheet and a glass fiber membrane; the positive electrode sheet is formed by coating a high-pressure compacted sodium iron phosphate pyrophosphate positive electrode material on an aluminum foil.

[0051] Preferably, the preparation of the positive electrode sheet of a sodium ion battery is specifically as follows:

[0052] The high-density sodium iron phosphate pyrophosphate positive electrode material is mixed with acetylene black and N-methylpyrrolidone / polyvinylidene fluoride mixed solution, the obtained mixture is fully ground and mixed in a small mortar, 10-20 zirconium dioxide beads with a diameter of 2-5 mm are added, and a mixed slurry is obtained by a micro-vibration ball mill, which is coated on aluminum foil and placed in a vacuum drying oven at 100-150°C for vacuum drying for 6-36 hours. After the solvent is completely evaporated, the sheet is cut to obtain a sodium ion battery positive electrode sheet.

[0053] More preferably, the N-methylpyrrolidone / polyvinylidene fluoride mixed solution comprises N-methylpyrrolidone and polyvinylidene fluoride, and the volume ratio of polyvinylidene fluoride to N-methylpyrrolidone is 1 g: 10-30 mL.

[0054] More preferably, the mass ratio of acetylene black to high-density sodium iron phosphate pyrophosphate positive electrode material is 1:20-40.

[0055] More preferably, the usage ratio of acetylene black and N-methylpyrrolidone / polyvinylidene fluoride mixed solution is 1 g: 0.5-2 mL.

[0056] The invention also discloses a vehicle, comprising a sodium ion battery.

[0057] The invention mixes sodium acetate, ferric oxalate, ammonium dihydrogen phosphate, polyethylene glycol, sucrose, nano titanium nitride and nano zirconium dioxide, and adds a slurry dispersant to prepare a high-density sodium phosphate iron pyrophosphate positive electrode material. The slurry dispersant includes a tetraphenylethylene quaternary ammonium salt derivative, an amide pyridine compound and polyethylene glycol triphenylphosphine, so that the high-density sodium phosphate iron pyrophosphate positive electrode material prepared by the invention has the following beneficial effects: the compaction density of the high-density sodium phosphate iron pyrophosphate positive electrode material prepared by the invention is 2.41-3.15 g / cm 3 , reversible capacity is 106.5-131.2mAh / g; the high-compacted sodium iron phosphate pyrophosphate positive electrode material prepared by the present invention has high compaction density and high reversible capacity, which can effectively improve its energy density and maintain the cycle stability of sodium ion batteries. Therefore, the present invention is a method for preparing a high-compacted sodium iron phosphate pyrophosphate positive electrode material with high compaction density and high reversible capacity and a vehicle. BRIEF DESCRIPTION OF THE DRAWINGS

[0058] Figure 1 The XRD diagrams of the high-density sodium iron pyrophosphate positive electrode materials obtained in Example 1 and Comparative Example 1 are shown.

[0059] Figure 2 The charge and discharge curves of the high-density sodium iron pyrophosphate positive electrode material obtained in Example 1 and Comparative Example 1.

[0060] Figure 3This is a rate performance diagram of the high-density sodium iron pyrophosphate positive electrode material obtained in Example 1 and Comparative Example 1.

[0061] Figure 4 This is a cycle life diagram of the high-density sodium iron pyrophosphate positive electrode material obtained in Example 1 and Comparative Example 1. DETAILED DESCRIPTION

[0062] The present invention is further described in detail below in conjunction with specific embodiments, and the examples provided are only for illustrating the present invention, rather than for limiting the scope of the present invention. The examples provided below can be used as a guide for further improvements by those of ordinary skill in the art, and do not constitute a limitation of the present invention in any way.

[0063] The experimental methods in the following examples are conventional methods unless otherwise specified. The materials, reagents, etc. used in the following examples are commercially available unless otherwise specified.

[0064] Embodiment 1:

[0065] A method for preparing a high-density sodium iron pyrophosphate positive electrode material comprises:

[0066] Sodium acetate, ferric oxalate, ammonium dihydrogen phosphate, polyethylene glycol, sucrose, nano titanium nitride and nano zirconium dioxide were mixed, deionized water was added, and the mixture was dispersed by high-speed stirring for 30 minutes. The mixture was treated by sand milling at a speed of 1500 rpm for 2 hours until it was evenly dispersed and the D50 particle size was 180 nm. The mixture was spray dried at a feed rate of 1.5 L / h at 220°C, and then the temperature was increased to 530°C at a rate of 2°C / min under a nitrogen atmosphere and sintered for 24 hours. The particles were crushed to a D50 particle size of 4.5 μm by air flow milling to obtain a high-density sodium iron phosphate pyrophosphate positive electrode material. The mass ratio of sodium acetate to ferrous oxalate is 1:3.5; the mass ratio of sodium acetate to diammonium phosphate is 1:1.5; the mass ratio of polyethylene glycol to diammonium phosphate is 1:30; the mass ratio of sucrose to diammonium phosphate is 1:30; the mass ratio of sodium acetate to nano-titanium nitride is 1:0.007; the mass ratio of nano-titanium nitride to nano-zirconium dioxide is 1:1; the usage ratio of sodium acetate to deionized water is 1g:5.5mL.

[0067] Embodiment 2:

[0068] Compared with Example 1, the present embodiment differs in that a method for preparing a high-density sodium iron pyrophosphate positive electrode material is provided.

[0069] A method for preparing a high-density sodium iron pyrophosphate positive electrode material comprises:

[0070] Sodium acetate, ferric oxalate, ammonium dihydrogen phosphate, polyethylene glycol, sucrose, nano titanium nitride, and nano zirconium dioxide are added to deionized water and mixed and stirred. A tetraphenylethylene quaternary ammonium salt derivative and an amide pyridine compound are added, and the mixture is dispersed with high-speed stirring for 30 minutes. The mixture is sand-milled at a speed of 1500 rpm for 2 hours until it is evenly dispersed and has a D50 particle size of 180 nm. The mixture is spray-dried at a feed rate of 1.5 L / h at 220°C, and then the temperature is raised to 530°C at a rate of 2°C / min under a nitrogen atmosphere and sintered for 24 hours. The particles are crushed to a D50 particle size of 4.5 μm by air flow milling to obtain a high-density sodium iron phosphate pyrophosphate positive electrode material. The mass ratio of sodium acetate to ferric oxalate is 1:3.5; the mass ratio of sodium acetate to ammonium dihydrogen phosphate is 1:1.5; the mass ratio of polyethylene glycol to ammonium dihydrogen phosphate is 1:30; the mass ratio of sucrose to ammonium dihydrogen phosphate is 1:30; the mass ratio of sodium acetate to nano titanium nitride is 1:0.007; the mass ratio of nano titanium nitride to nano zirconium dioxide is 1:1; the dosage ratio of sodium acetate to deionized water is 1g:5.5mL; the mass ratio of sodium acetate to tetraphenylethylene quaternary ammonium salt derivative is 1:0.04; the mass ratio of tetraphenylethylene quaternary ammonium salt derivative to amide pyridine compound is 1:1. The preparation method of tetraphenylethylene quaternary ammonium salt derivative and amide pyridine compound is as follows:

[0071] A method for preparing a tetraphenylethylene quaternary ammonium salt derivative comprises:

[0072] 1,1-diphenyl-2,2-di(4-bromophenyl)ethylene and N-(3-(dimethylamino)propyl)octanamide were mixed, acetone was added, heated to reflux for 48h, rotary evaporated, and vacuum dried to obtain a tetraphenylethylene quaternary ammonium salt derivative. The molar ratio of 1,1-diphenyl-2,2-di(4-bromophenyl)ethylene and N-(3-(dimethylamino)propyl)octanamide was 1:2; the amount ratio of 1,1-diphenyl-2,2-di(4-bromophenyl)ethylene and acetone was 1mmol:1.5mL.

[0073] A method for preparing an amide pyridine compound, comprising:

[0074] Ethyl isonicotinate and 1,6-diaminohexane are mixed, sodium methoxide solution and toluene are added, reflux reaction is carried out for 12 hours, 1,4-dichlorobutane and N,N-dimethylformamide are added, heating is carried out at 120°C for 12 hours, and recrystallization is carried out for 3 times by adding a recrystallization agent to obtain an amide pyridine compound. The molar ratio of ethyl isonicotinate to 1,6-diaminohexane is 1:0.5; the mass concentration of the sodium methoxide solution is 28%, the dosage ratio of ethyl isonicotinate to the sodium methoxide solution is 1 mol:100 mL; the volume ratio of the sodium methoxide solution to toluene is 1:10; the molar ratio of ethyl isonicotinate to 1,4-dichlorobutane is 1:2.2; the volume ratio of the sodium methoxide solution to N,N-dimethylformamide is 1:10; the volume ratio of toluene to the recrystallization agent is 1:2, and the recrystallization agent includes acetone and methanol, and the volume ratio of acetone to methanol is 1:1.

[0075] Embodiment 3:

[0076] Compared with Example 2, the difference between this embodiment and Example 2 lies in a method for preparing a high-density sodium iron pyrophosphate positive electrode material.

[0077] In this embodiment, except that the mass ratio of sodium acetate to tetraphenylethylene quaternary ammonium salt derivative is changed to 1:0.02, other conditions are the same as those in Embodiment 2.

[0078] Embodiment 4:

[0079] Compared with Example 2, the difference between this embodiment and Example 2 lies in a method for preparing a high-density sodium iron pyrophosphate positive electrode material.

[0080] In this embodiment, except that the mass ratio of the tetraphenylethylene quaternary ammonium salt derivative and the amide pyridine compound is changed to 1:0.5, other conditions are the same as those in Embodiment 2.

[0081] Embodiment 5:

[0082] Compared with Example 1, the present embodiment differs in that a method for preparing a high-density sodium iron pyrophosphate positive electrode material is provided.

[0083] A method for preparing a high-density sodium iron pyrophosphate positive electrode material comprises:

[0084] Sodium acetate, ferric oxalate, ammonium dihydrogen phosphate, polyethylene glycol, sucrose, nano titanium nitride, and nano zirconium dioxide are added to deionized water and mixed and stirred. Tetraphenylethylene quaternary ammonium salt derivatives, amide pyridine compounds, and polyethylene glycol triphenylphosphine are added, and the mixture is dispersed with high-speed stirring for 30 minutes. The mixture is sand-milled at a speed of 1500 rpm for 2 hours until it is evenly dispersed and has a D50 particle size of 180 nm. The mixture is spray-dried at a feed rate of 1.5 L / h at 220°C, and then the temperature is raised to 530°C at a rate of 2°C / min under a nitrogen atmosphere and sintered for 24 hours. The particles are crushed to a D50 particle size of 4.5 μm by air flow milling to obtain a high-density sodium iron phosphate pyrophosphate positive electrode material. The mass ratio of sodium acetate to ferric oxalate is 1:3.5; the mass ratio of sodium acetate to ammonium dihydrogen phosphate is 1:1.5; the mass ratio of polyethylene glycol to ammonium dihydrogen phosphate is 1:30; the mass ratio of sucrose to ammonium dihydrogen phosphate is 1:30; the mass ratio of sodium acetate to nano titanium nitride is 1:0.007; the mass ratio of nano titanium nitride to nano zirconium dioxide is 1:1; the dosage ratio of sodium acetate to deionized water is 1g:5.5mL; the mass ratio of sodium acetate to tetraphenylethylene quaternary ammonium salt derivative is 1:0.04; the mass ratio of tetraphenylethylene quaternary ammonium salt derivative to amide pyridine compound is 1:1; the mass ratio of tetraphenylethylene quaternary ammonium salt derivative to polyethylene glycol triphenylphosphine is 1:0.5. The preparation method of tetraphenylethylene quaternary ammonium salt derivative and amide pyridine compound is as follows:

[0085] A method for preparing a tetraphenylethylene quaternary ammonium salt derivative comprises:

[0086] 1,1-diphenyl-2,2-di(4-bromophenyl)ethylene and N-(3-(dimethylamino)propyl)octanamide were mixed, acetone was added, heated to reflux for 48h, rotary evaporated, and vacuum dried to obtain a tetraphenylethylene quaternary ammonium salt derivative. The molar ratio of 1,1-diphenyl-2,2-di(4-bromophenyl)ethylene and N-(3-(dimethylamino)propyl)octanamide was 1:2; the amount ratio of 1,1-diphenyl-2,2-di(4-bromophenyl)ethylene and acetone was 1mmol:1.5mL.

[0087] A method for preparing an amide pyridine compound, comprising:

[0088] Ethyl isonicotinate and 1,6-diaminohexane are mixed, sodium methoxide solution and toluene are added, reflux reaction is carried out for 12 hours, 1,4-dichlorobutane and N,N-dimethylformamide are added, heating is carried out at 120°C for 12 hours, and recrystallization is carried out for 3 times by adding a recrystallization agent to obtain an amide pyridine compound. The molar ratio of ethyl isonicotinate to 1,6-diaminohexane is 1:0.5; the mass concentration of the sodium methoxide solution is 28%, the dosage ratio of ethyl isonicotinate to the sodium methoxide solution is 1 mol:100 mL; the volume ratio of the sodium methoxide solution to toluene is 1:10; the molar ratio of ethyl isonicotinate to 1,4-dichlorobutane is 1:2.2; the volume ratio of the sodium methoxide solution to N,N-dimethylformamide is 1:10; the volume ratio of toluene to the recrystallization agent is 1:2, and the recrystallization agent includes acetone and methanol, and the volume ratio of acetone to methanol is 1:1.

[0089] Embodiment 6:

[0090] Compared with Example 5, the present embodiment differs in that a method for preparing a high-density sodium iron pyrophosphate positive electrode material is provided.

[0091] In this embodiment, except that the mass ratio of the tetraphenylethylene quaternary ammonium salt derivative and polyethylene glycol triphenylphosphine is changed to 1:0.25, other conditions are the same as those in Embodiment 5.

[0092] Comparative Example 1:

[0093] Compared with Example 1, this comparative example differs in that a method for preparing a high-density sodium iron pyrophosphate positive electrode material is provided.

[0094] A method for preparing a high-density sodium iron pyrophosphate positive electrode material comprises:

[0095] Sodium acetate, ferrous oxalate, ammonium dihydrogen phosphate, polyethylene glycol, and sucrose were added to deionized water and mixed and stirred, and dispersed at high speed for 30 minutes. The mixture was treated at a sand mill speed of 1500 rpm for 2 hours until it was evenly dispersed and the D50 particle size was 180 nm. The mixture was spray dried at a feed rate of 1.5 L / h at 220 ° C, and then sintered at a temperature of 530 ° C at a rate of 2 ° C / min for 24 hours under a nitrogen atmosphere. The particles were crushed to a D50 particle size of 4.5 μm by air flow milling to obtain a high-density sodium iron phosphate pyrophosphate cathode material. The mass ratio of sodium acetate to ferrous oxalate was 1:3.5; the mass ratio of sodium acetate to ammonium dihydrogen phosphate was 1:1.5; the mass ratio of polyethylene glycol to ammonium dihydrogen phosphate was 1:30; the mass ratio of sucrose to ammonium dihydrogen phosphate was 1:30; and the dosage ratio of sodium acetate to deionized water was 1 g:5.5 mL.

[0096] Comparative Example 2:

[0097] Compared with Example 1, this comparative example differs in that a method for preparing a high-density sodium iron pyrophosphate positive electrode material is provided.

[0098] A method for preparing a high-density sodium iron pyrophosphate positive electrode material comprises:

[0099] Sodium acetate, ferric oxalate, ammonium dihydrogen phosphate, polyethylene glycol, sucrose, nano titanium nitride, and nano zirconium dioxide are added to deionized water and mixed and stirred. A tetraphenylethylene quaternary ammonium salt derivative is added, and the mixture is dispersed with high-speed stirring for 30 minutes. The mixture is sand-milled at a speed of 1500 rpm for 2 hours until it is evenly dispersed and has a D50 particle size of 180 nm. The mixture is spray-dried at a feed rate of 1.5 L / h at 220°C, and then the temperature is raised to 530°C at a rate of 2°C / min under a nitrogen atmosphere and sintered for 24 hours. The particles are crushed to a D50 particle size of 4.5 μm by air flow milling to obtain a high-density sodium iron phosphate pyrophosphate positive electrode material. The mass ratio of sodium acetate to ferrous oxalate is 1:3.5; the mass ratio of sodium acetate to ammonium dihydrogen phosphate is 1:1.5; the mass ratio of polyethylene glycol to ammonium dihydrogen phosphate is 1:30; the mass ratio of sucrose to ammonium dihydrogen phosphate is 1:30; the mass ratio of sodium acetate to nano titanium nitride is 1:0.007; the mass ratio of nano titanium nitride to nano zirconium dioxide is 1:1; the dosage ratio of sodium acetate to deionized water is 1g:5.5mL; the mass ratio of sodium acetate to tetraphenylethylene quaternary ammonium salt derivative is 1:0.04. The preparation method of tetraphenylethylene quaternary ammonium salt derivative is as follows:

[0100] A method for preparing a tetraphenylethylene quaternary ammonium salt derivative comprises:

[0101] 1,1-diphenyl-2,2-di(4-bromophenyl)ethylene and N-(3-(dimethylamino)propyl)octanamide were mixed, acetone was added, heated to reflux for 48h, rotary evaporated, and vacuum dried to obtain a tetraphenylethylene quaternary ammonium salt derivative. The molar ratio of 1,1-diphenyl-2,2-di(4-bromophenyl)ethylene and N-(3-(dimethylamino)propyl)octanamide was 1:2; the amount ratio of 1,1-diphenyl-2,2-di(4-bromophenyl)ethylene and acetone was 1mmol:1.5mL.

[0102] Comparative Example 3:

[0103] Compared with Example 1, the difference between this comparative example and Example 1 lies in a method for preparing a high-density sodium iron pyrophosphate positive electrode material.

[0104] A method for preparing a high-density sodium iron pyrophosphate positive electrode material comprises:

[0105] Sodium acetate, ferric oxalate, ammonium dihydrogen phosphate, polyethylene glycol, sucrose, nano titanium nitride, and nano zirconium dioxide are added to deionized water and mixed and stirred. An amide pyridine compound is added and dispersed with high-speed stirring for 30 minutes. The mixture is sand-milled at a speed of 1500 rpm for 2 hours until it is evenly dispersed and has a D50 particle size of 180 nm. The mixture is spray-dried at a feed rate of 1.5 L / h at 220°C. The temperature is then raised to 530°C at a rate of 2°C / min under a nitrogen atmosphere and sintered for 24 hours. The particles are crushed to a D50 particle size of 4.5 μm using airflow milling to obtain a high-density sodium iron phosphate pyrophosphate cathode material. The mass ratio of sodium acetate to ferrous oxalate is 1:3.5; the mass ratio of sodium acetate to ammonium dihydrogen phosphate is 1:1.5; the mass ratio of polyethylene glycol to ammonium dihydrogen phosphate is 1:30; the mass ratio of sucrose to ammonium dihydrogen phosphate is 1:30; the mass ratio of sodium acetate to nano titanium nitride is 1:0.007; the mass ratio of nano titanium nitride to nano zirconium dioxide is 1:1; the dosage ratio of sodium acetate to deionized water is 1g:5.5mL; the mass ratio of sodium acetate to amide pyridine compound is 1:0.04. The preparation method of amide pyridine compound is as follows:

[0106] A method for preparing an amide pyridine compound, comprising:

[0107] Ethyl isonicotinate and 1,6-diaminohexane are mixed, sodium methoxide solution and toluene are added, reflux reaction is carried out for 12 hours, 1,4-dichlorobutane and N,N-dimethylformamide are added, heating is carried out at 120°C for 12 hours, and recrystallization is carried out for 3 times by adding a recrystallization agent to obtain an amide pyridine compound. The molar ratio of ethyl isonicotinate to 1,6-diaminohexane is 1:0.5; the mass concentration of the sodium methoxide solution is 28%, the dosage ratio of ethyl isonicotinate to the sodium methoxide solution is 1 mol:100 mL; the volume ratio of the sodium methoxide solution to toluene is 1:10; the molar ratio of ethyl isonicotinate to 1,4-dichlorobutane is 1:2.2; the volume ratio of the sodium methoxide solution to N,N-dimethylformamide is 1:10; the volume ratio of toluene to the recrystallization agent is 1:2, and the recrystallization agent includes acetone and methanol, and the volume ratio of acetone to methanol is 1:1.

[0108] Comparative Example 4:

[0109] Compared with Example 1, this comparative example differs in that a method for preparing a high-density sodium iron pyrophosphate positive electrode material is provided.

[0110] A method for preparing a high-density sodium iron pyrophosphate positive electrode material comprises:

[0111] Sodium acetate, ferric oxalate, ammonium dihydrogen phosphate, polyethylene glycol, sucrose, nano titanium nitride, and nano zirconium dioxide are added to deionized water and mixed and stirred. Polyethylene glycol triphenylphosphine is added and dispersed with high-speed stirring for 30 minutes. The mixture is treated with a sand mill at a speed of 1500 rpm for 2 hours until it is evenly dispersed and the D50 particle size is 180 nm. The mixture is spray dried at a feed rate of 1.5 L / h at 220°C. The temperature is then increased to 530°C at a rate of 2°C / min under a nitrogen atmosphere and sintered for 24 hours. The particles are crushed to a D50 particle size of 4.5 μm using air flow milling to obtain a high-density sodium iron phosphate pyrophosphate positive electrode material. The mass ratio of sodium acetate to ferric oxalate is 1:3.5; the mass ratio of sodium acetate to diammonium phosphate is 1:1.5; the mass ratio of polyethylene glycol to diammonium phosphate is 1:30; the mass ratio of sucrose to diammonium phosphate is 1:30; the mass ratio of sodium acetate to nano-titanium nitride is 1:0.007; the mass ratio of nano-titanium nitride to nano-zirconium dioxide is 1:1; the dosage ratio of sodium acetate to deionized water is 1g:5.5mL; the mass ratio of sodium acetate to polyethylene glycol triphenylphosphine is 1:0.02.

[0112] Experimental example:

[0113] Preparation of positive electrode sheet for sodium ion battery: Highly compacted sodium iron phosphate pyrophosphate positive electrode material is mixed with acetylene black and N-methylpyrrolidone / polyvinylidene fluoride mixed solution, the obtained mixture is fully ground and mixed in a small mortar, 15 zirconium dioxide beads with a diameter of 3 mm are added, and a mixed slurry is obtained by a micro-vibration ball mill, which is coated on aluminum foil and placed in a vacuum drying oven at 120°C for vacuum drying for 12 hours. After the solvent is completely evaporated, the sheet is cut to obtain a positive electrode sheet for sodium ion battery. The N-methylpyrrolidone / polyvinylidene fluoride mixed solution includes N-methylpyrrolidone and polyvinylidene fluoride, and the volume ratio of polyvinylidene fluoride to N-methylpyrrolidone is 1g:20mL; the mass ratio of acetylene black to high-compacted sodium iron phosphate pyrophosphate positive electrode material is 1:31; the amount ratio of acetylene black to N-methylpyrrolidone / polyvinylidene fluoride mixed solution is 1g:1mL.

[0114] Preparation of sodium ion battery: The prepared sodium ion battery positive electrode sheet is used as the battery positive electrode, the glass fiber membrane is used as the separator, the sodium sheet is used as the battery negative electrode, the electrolyte includes sodium perchlorate, fluoroethylene carbonate and propylene carbonate, the dosage ratio of sodium perchlorate to propylene carbonate is 1 mol:1L, and the dosage ratio of fluoroethylene carbonate to propylene carbonate is 1 g:20mL.

[0115] 1. Material Characterization

[0116] At room temperature, the high-density sodium iron phosphate pyrophosphate positive electrode materials prepared in Example 1 and Comparative Example 1 were used to prepare sodium ion battery positive electrode sheets, and the diffraction phenomenon in the sodium ion battery positive electrode sheets was tested by X-rays, using a copper target as the emission source, a scanning range of 10°-90°, a scanning speed of 5° / min, and a wavelength set to 0.15418nm.

[0117] Figure 1 The XRD diagrams of the high-pressure compacted sodium iron phosphate pyrophosphate positive electrode materials obtained in Example 1 and Comparative Example 1. The main characteristic peaks of the high-pressure compacted sodium iron phosphate pyrophosphate positive electrode materials obtained in Example 1 of the present invention and Comparative Example 1 are basically the same, except that Comparative Example 1 has characteristic peaks belonging to the inactive impurity M-NaFePO4, which are 20.2° (212), 32.8° (220) and 33.0° (121) characteristic peaks. The difference between Example 1 and Comparative Example 1 is that in the preparation of the high-pressure compacted sodium iron phosphate pyrophosphate positive electrode material, Example 1 uses nano-titanium nitride and nano-zirconium dioxide as second-phase nanoparticles, while Comparative Example 1 does not use nano-titanium nitride and nano-zirconium dioxide. This shows that in the preparation of the high-pressure compacted sodium iron phosphate pyrophosphate positive electrode material, the introduction of nano-titanium nitride and nano-zirconium dioxide helps to suppress the generation of the inactive impurity M-NaFePO4.

[0118] 2. Compacted density

[0119] Compacting the electrode sheet can reduce the thickness of the electrode sheet and increase the energy density of the sodium ion positive electrode sheet; at the same time, increasing the compaction density of the positive electrode sheet can enhance the contact effect between the conductive agent and the main material, and improve the electronic conductivity of the electrode material during the charging and discharging process.

[0120] At room temperature, the high-density sodium iron phosphate pyrophosphate positive electrode materials prepared in Examples 1-6 and Comparative Examples 1-4 were used to prepare positive electrode sheets for sodium ion batteries, and the compaction densities of the positive electrode sheets for sodium ion batteries obtained in Examples 1-6 and Comparative Examples 1-4 were calculated. Compacted density (g / cm 3 ) = surface density (mg / cm 2 ) / thickness (μm), the measurement results are shown in Table 1.

[0121] Table 1 Compacted density (g / cm 3 )

[0122]

[0123] As can be seen from Table 1, the compaction density of Example 1 of the present invention is higher than that of Comparative Example 1. The difference between Example 1 and Comparative Example 1 is that in the preparation of the high-pressure compacted sodium iron phosphate pyrophosphate positive electrode material, Example 1 uses nano titanium nitride and nano zirconium dioxide as the second phase nanoparticles, while Comparative Example 1 does not use nano titanium nitride and nano zirconium dioxide. This shows that in the preparation of the high-pressure compacted sodium iron phosphate pyrophosphate positive electrode material, the introduction of nano titanium nitride and nano zirconium dioxide helps to increase the compaction density of the sodium ion battery positive electrode material.

[0124] The compaction density of Examples 2-4 of the present invention is higher than that of Example 1. The difference between Examples 2-4 and Example 1 is that in the preparation of the high-compacted sodium iron phosphate pyrophosphate positive electrode material, Examples 2-4 additionally use tetraphenylethylene quaternary ammonium salt derivatives and amide pyridine compounds as slurry dispersants to prepare the high-compacted sodium iron phosphate pyrophosphate positive electrode material, while Example 1 does not use tetraphenylethylene quaternary ammonium salt derivatives and amide pyridine compounds; the compaction density of Example 2 is higher than that of Examples 3-4. The difference between Examples 2 and Examples 3-4 is that the high-compacted sodium iron phosphate pyrophosphate In the preparation of sodium positive electrode materials, the amount of tetraphenylethylene quaternary ammonium salt derivatives and amide pyridine compounds used is different; the compaction density of Examples 2-4 is higher than that of Comparative Examples 2-3, and the difference between Examples 2-4 and Comparative Examples 2-3 is that in the preparation of high-pressure compacted sodium iron phosphate pyrophosphate positive electrode materials, Examples 2-4 use tetraphenylethylene quaternary ammonium salt derivatives and amide pyridine compounds as slurry dispersants, while Comparative Example 2 only uses tetraphenylethylene quaternary ammonium salt derivatives as slurry dispersants, and Comparative Example 3 only uses amide pyridine compounds as slurry dispersants. This shows that in the preparation of high-pressure compacted sodium iron phosphate pyrophosphate positive electrode materials, the coordinated use of tetraphenylethylene quaternary ammonium salt derivatives and amide pyridine compounds as slurry dispersants helps to increase the compaction density of sodium ion battery positive electrode materials.

[0125] The compaction density of Examples 5-6 of the present invention is higher than that of Example 2. The difference between Examples 5-6 and Example 2 is that in the preparation of the high-pressure compacted sodium iron phosphate pyrophosphate positive electrode material, Example 5-6 further uses polyethylene glycol triphenylphosphine as a slurry dispersant; the compaction density of Example 5 is higher than that of Example 6 because the amount of polyethylene glycol triphenylphosphine used is different; the compaction density of Examples 5-6 is higher than that of Comparative Example 4. The difference between Examples 5-6 and Comparative Example 4 is that in the preparation of the high-pressure compacted sodium iron phosphate pyrophosphate positive electrode material, Examples 5-6 use tetrastyryl quaternary ammonium salt derivatives, amide pyridine compounds and polyethylene glycol triphenylphosphine as slurry dispersants, and Comparative Example 4 only uses polyethylene glycol triphenylphosphine as a slurry dispersant. This shows that in the preparation of the high-pressure compacted sodium iron phosphate pyrophosphate positive electrode material, further using polyethylene glycol triphenylphosphine as a slurry dispersant can further increase the compaction density of the sodium ion battery positive electrode material.

[0126] 3. Electrochemical performance test

[0127] At room temperature, sodium ion batteries were assembled using the high-density sodium iron phosphate pyrophosphate positive electrode materials prepared in Examples 1-6 and Comparative Examples 1-4, respectively. Constant current charge and discharge tests, rate performance tests, and cycle life tests were performed on the sodium ion batteries prepared in Examples 1-6 and Comparative Examples 1-4 in turn using a Newway CT4000. The voltage test window was 2.0-4.0V (vs. Na + / Na), and the test current densities for rate performance are 10mA / g, 20mA / g, 50mA / g, 100mA / g, 150mA / g, 200mA / g, 300mA / g, 500mA / g and 1000mA / g.

[0128] Figure 2 The charge and discharge curves of the high-density sodium iron pyrophosphate positive electrode materials obtained in Example 1 and Comparative Example 1 are shown, with a current density of 50 mA / g. The solid line in the figure is the charge and discharge curve of Example 1, and the dotted line is the charge and discharge curve of Comparative Example 1. Figure 3 The figure is a rate performance diagram of the charge and discharge curves of the high-compacted sodium iron phosphate pyrophosphate positive electrode materials obtained in Example 1 and Comparative Example 1. At the same current density, the reversible capacity of Example 1 is higher than that of Comparative Example 1. Figure 4 The cycle life of the charge and discharge curves of the high-compacted sodium iron phosphate pyrophosphate positive electrode material obtained in Example 1 and Comparative Example 1, at a current density of 50 mA / g, the reversible capacity of Example 1 is 106.5 mAh / g, the reversible capacity at the 200th cycle is 106.5 mAh / g, and the capacity retention rate is 100%; the reversible capacity of Comparative Example 1 is 90.2 mAh / g, the reversible capacity at the 200th cycle is 68.6 mAh / g, and the capacity retention rate is 76.1%.

[0129] Table 2 Reversible capacity (mAh / g)

[0130]

[0131] As can be seen from Table 2, the reversible capacity of Example 1 of the present invention is higher than that of Comparative Example 1. The difference between Example 1 and Comparative Example 1 is that in the preparation of the high-pressure compacted sodium iron phosphate pyrophosphate positive electrode material, Example 1 uses nano titanium nitride and nano zirconium dioxide as the second phase nanoparticles, while Comparative Example 1 does not use nano titanium nitride and nano zirconium dioxide. This shows that in the preparation of the high-pressure compacted sodium iron phosphate pyrophosphate positive electrode material, the introduction of nano titanium nitride and nano zirconium dioxide helps to increase the reversible capacity of the sodium ion battery positive electrode material.

[0132] The reversible capacity of Examples 2-4 of the present invention is higher than that of Example 1. The difference between Examples 2-4 and Example 1 is that in the preparation of the high-density phosphate sodium iron pyrophosphate positive electrode material, Examples 2-4 additionally use tetraphenylethylene quaternary ammonium salt derivatives and amide pyridine compounds as slurry dispersants to prepare the high-density phosphate sodium iron pyrophosphate positive electrode material, while Example 1 does not use tetraphenylethylene quaternary ammonium salt derivatives and amide pyridine compounds; The reversible capacity of Example 2 is higher than that of Examples 3-4. The difference between Examples 2 and Examples 3-4 is that the high-density phosphate iron pyrophosphate In the preparation of sodium positive electrode materials, the amount of tetrastyryl quaternary ammonium salt derivatives and amide pyridine compounds used is different; the reversible capacity of Examples 2-4 is higher than that of Comparative Examples 2-3, and the difference between Examples 2-4 and Comparative Examples 2-3 is that in the preparation of high-density phosphate sodium iron pyrophosphate positive electrode materials, Examples 2-4 use tetrastyryl quaternary ammonium salt derivatives and amide pyridine compounds as slurry dispersants, while Comparative Example 2 only uses tetrastyryl quaternary ammonium salt derivatives as slurry dispersants, and Comparative Example 3 only uses amide pyridine compounds as slurry dispersants. This shows that in the preparation of high-density phosphate sodium iron pyrophosphate positive electrode materials, the coordinated use of tetrastyryl quaternary ammonium salt derivatives and amide pyridine compounds as slurry dispersants helps to increase the reversible capacity of the positive electrode material of the sodium ion battery.

[0133] The reversible capacity of Examples 5-6 of the present invention is higher than that of Example 2. The difference between Examples 5-6 and Example 2 is that in the preparation of the high-density sodium iron phosphate pyrophosphate positive electrode material, Example 5-6 further uses polyethylene glycol triphenylphosphine as a slurry dispersant; the reversible capacity of Example 5 is higher than that of Example 6 because the amount of polyethylene glycol triphenylphosphine used is different; the reversible capacity of Examples 5-6 is higher than that of Comparative Example 4. The difference between Examples 5-6 and Comparative Example 4 is that in the preparation of the high-density sodium iron phosphate pyrophosphate positive electrode material, Examples 5-6 use tetraphenylethylene quaternary ammonium salt derivatives, amide pyridine compounds and polyethylene glycol triphenylphosphine as slurry dispersants, and Comparative Example 4 only uses polyethylene glycol triphenylphosphine as a slurry dispersant. This shows that in the preparation of the high-density sodium iron phosphate pyrophosphate positive electrode material, further using polyethylene glycol triphenylphosphine as a slurry dispersant can further increase the reversible capacity of the sodium ion battery positive electrode material.

[0134] The conventional operations in the operating steps of the present invention are well known to those skilled in the art and will not be described in detail here.

[0135] The embodiments described above provide a detailed description of the technical solutions of the present invention. It should be understood that the above are only specific embodiments of the present invention and are not intended to limit the present invention. Any modifications, supplements or similar substitutions made within the scope of the principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a high-density sodium iron phosphate pyrophosphate cathode material, comprising: uniformly mixing a metal compound, a non-metal compound, a second phase nanoparticle and deionized water, adding a slurry dispersant and stirring at high speed, and then sand milling, spray drying and air flow pulverizing to obtain a high-density sodium iron phosphate pyrophosphate cathode material; the second phase nanoparticles include nano titanium nitride and nano zirconium dioxide, the mass ratio of the nano titanium nitride to the nano zirconium dioxide is 1:1-2; the slurry dispersant includes at least a tetraphenylethylene quaternary ammonium salt derivative and an amide pyridine compound; the tetraphenylethylene quaternary In the preparation of the ammonium salt derivative, 1,1-diphenyl-2,2-di(4-bromophenyl)ethylene and N-(3-(dimethylamino)propyl)octanamide are mixed, acetone is added, and the mixture is heated under reflux for 36-72 hours to obtain a tetraphenylethylene quaternary ammonium salt derivative; in the preparation of the amide pyridine compound, ethyl isonicotinate and 1,6-diaminohexane are mixed, sodium methoxide solution and toluene are added, the mixture is refluxed for 8-24 hours, 1,4-dichlorobutane and N,N-dimethylformamide are added, and the mixture is heated at 100-150° C. for 8-24 hours to obtain an amide pyridine compound.

2. The method for preparing a high-density sodium iron phosphate pyrophosphate positive electrode material according to claim 1, characterized in that: The metal compound comprises sodium acetate and ferric oxalate, and the mass ratio of sodium acetate to ferric oxalate is 1:2-10.

3. The method for preparing a high-density sodium iron phosphate pyrophosphate positive electrode material according to claim 1, characterized in that: The non-metallic compound comprises diammonium phosphate, polyethylene glycol and sucrose, the mass ratio of polyethylene glycol to diammonium phosphate is 1:20-40, and the mass ratio of sucrose to diammonium phosphate is 1:20-40.

4. The method for preparing a high-density sodium iron pyrophosphate positive electrode material according to claim 1, characterized in that: The mass ratio of the tetraphenylethylene quaternary ammonium salt derivative to the amide pyridine compound is 1:1-2.

5. The high-density sodium iron phosphate pyrophosphate positive electrode material prepared by the preparation method according to any one of claims 1 to 4.

6. A sodium ion battery, comprising a sodium ion battery positive electrode sheet, a sodium sheet and a glass fiber membrane; the sodium ion battery positive electrode sheet is formed by coating the high-density phosphate sodium iron pyrophosphate positive electrode material according to claim 5 on an aluminum foil.

7. A vehicle comprising the sodium ion battery according to claim 6.

Citation Information

Patent Citations

  • PolyElectrolyte Composition and Methods of Preparation Thereof

    US20230378532A1

  • Deposited sodium iron phosphate positive electrode material, and preparation method therefor and application thereof

    WO2023060989A1